The Effect of NAA, BAP and NAA, BAP Combinations on the Growth of In-vitro Culturally Promoted Leaves of Sansevieria ehrenbergii - Fatikha Ajeng Safitr; Tengku Nurhidayah (Talenta Publisher, 2023)
Sansevieria is an ornamental succulent leaf plant of the family Agavaceae, having a beautiful and diverse shape and color. Propagation of Sansevieria can be done by tissue culture method with the addition of cytokinins and auxins to MS media. The study used a complete randomized design consisting of 8 treatments, 3 tests, there were 24 experimental units. The observed parameters are when the callus appears, the color of the callus, the texture of the callus, the weight of the callus, the diameter of the callus, and the percentage of success in growing. Data analysis used variance analysis and tested using 5% DNMRT. The data is processed using a Statistical Analysis System (SAS). The results showed that the application of NAA, BAP, and the combination of NAA and BAP affected the per-plant explant of Sansevieria ehrenbergii leaves on all observation parameters. The treatment of NAA 2 mg.l-1 + BAP 1 mg.l-1 gave effect tending to be faster when callus appeared with an average of 75.75 HST, NAA 1 mg.l-1 + BAP 2 mg.l-1 m. and tends to be larger in callus diameter with an average of 0.9033 g and 19.133 mm and NAA 1 mg.l-1 + BAP 1 mg.l-1 gives a higher influence on the percentage of callus growth by an average of 100 %.